2017
DOI: 10.4209/aaqr.2016.01.0029
|View full text |Cite
|
Sign up to set email alerts
|

A Chamber Study of Secondary Organic Aerosol (SOA) Formed by Ozonolysis of d-Limonene in the Presence of NO

Abstract: Experiments were conducted in a dynamic chamber system to measure the formation of secondary organic aerosol (SOA) and particle-bound reactive oxygen species (ROS) produced from limonene ozonolysis in the presence of NO by varying the ratio of O 3 to NO. A diffusion cell system was used to produce the constant input of limonene in to the chamber, and six sets of experiments were conducted. The concentration of SOA mass and ROS produced were measured at steady-state. ROS, including peroxides, peroxy radicals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…SOA data (see Table S1) were compiled from 12 published chamber studies (e.g., Chen et al, 2017;Griffin et al, 1999;Kim and Paulson, 2013;Kourtchev et al, 2014;Ng et al, 2007;Yu et al, 1999) in which α-pinene or limonene was used as a precursor and final SOA mass, SOA yield, and reacted hydrocarbon concentration (HC) were reported (at least two of the three quantities). For the α-pinene photooxidation data, there is an apparent cluster around an SOA yield of 0.2 for SOA mass < 150 µg m -3 with which the model agrees (Fig.…”
Section: Model-measurement Comparisonmentioning
confidence: 99%
“…SOA data (see Table S1) were compiled from 12 published chamber studies (e.g., Chen et al, 2017;Griffin et al, 1999;Kim and Paulson, 2013;Kourtchev et al, 2014;Ng et al, 2007;Yu et al, 1999) in which α-pinene or limonene was used as a precursor and final SOA mass, SOA yield, and reacted hydrocarbon concentration (HC) were reported (at least two of the three quantities). For the α-pinene photooxidation data, there is an apparent cluster around an SOA yield of 0.2 for SOA mass < 150 µg m -3 with which the model agrees (Fig.…”
Section: Model-measurement Comparisonmentioning
confidence: 99%
“…Chen and Hopke (2010) and Chen et al (2011Chen et al ( , 2017 studied ROS formation from the ozonolysis of limonene using a similar chemical assay with an offline filter sampling and sonication and filter extraction method. Like the current study, both short-lived and long-lived ROS are reported.…”
Section: Comparison To Other Studies Of Ros Formation In Soamentioning
confidence: 99%
“…Nitrogen oxides (NO x ) emitted from automobile and coal-fired power plant cause a variety of environmental problems, such as acid rain, photochemical smog, secondary organic aerosols and ozone depletion (Chen et al, 2017;Huang et al, 2017). To reduce air pollution resulted from NO x , advances in NO x removal technology have drawn much attention and been quite rapid.…”
Section: Introductionmentioning
confidence: 99%